A retrospective on Culture’s Consequences: The 35-year journey - Kirkman, Bradley L; Lowe, Kevin B; Gibson, Cristina B (Journal of International Business Studies, 2017)
Our 2006 Journal of International Business Studies article, “A Quarter Century of Culture’s Consequences: A Review of the Empirical Research Incorporating Hofstede’s Cultural Values Framework,” provided a comprehensive review of 180 empirical journal articles and edited volume chapters published between 1980 and June 2002 that incorporated Hofstede’s cross-cultural values framework. We examined empirical research that positioned culture as either a main or moderating effect. The review attempted to make sense of the almost quarter century of research examining the impact of culture at the individual, group/organization, and country levels. In the present commentary, we provide: (a) a summary of the progress that has been made in the intervening decade, and most importantly, (b) a new set of recommendations for the next decade to guide those wishing to study the role of national culture in organizations.